Hydrothermal Synthesis and Structure of Tetraazamacrocyclic Copper Complex - Wang, Lin; Li, Bai-Zhong; Bi, Jian-Hong; Dong, Hua-Ze (Asian Journal of Chemistry, 2015)
A new tetraazamacrocycle copper(II) complex with the m.f. C24H40N8S4Cu2 was synthesized by hydrothermal reaction and characterized by IR spectra and single-crystal X-ray diffraction. The crystal is in a triclinic system, space group P-1 with unit cell parameters: a = 8.861(3)Å, b = 18.832(7)Å, c = 20.826(6)Å, a = 74.194(12)º, b = 80.025(13)º, g = 79.714(9)º, V = 3261.5(19)Å3, Z = 4, Mr = 695.96, Dc = 1.417 Mg/cm3, μ = 1.588 mm-1, F(000) = 1448, T = 298(2) K, R = 0.0695, wR = 0.1584 for 11405 reflections with I > 2s(I). The crystal structure analysis shows that the Cu(II) ion was coordinated by four nitrogen atoms of the tetraazamacrocycle.